Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s13277-014-3033-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cystatin SN as a novel biomarker for pancreatic cancer

Abstract: Cystatin SN (cystatin 1, CST1) is a member of the cystatin superfamily that inhibits the proteolytic activity of cysteine proteases. CST1 is a tumor biomarker that provides useful information for the diagnosis of esophageal, gastric, and colorectal carcinomas. However, the significance of CST1 in pancreatic cancer is unknown. The aim of this study was to assess whether CST1 is a potential biomarker for early diagnosis of malignant pancreatic neoplasms. Microarray analysis of mRNA extracted from pancreatic canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 26 publications
4
40
0
Order By: Relevance
“…In accordance with this, the Kaplan–Meier survival analysis demonstrated that the OS and DFS of breast cancer patients with high CST1 expression were worse than those with low CST1 expression. High CST1 expression was also reported by previous studies to be linked to poor survival in colorectal cancer [40], pancreatic cancer [41], and non-small cell lung cancer patients [42], which was consistent with our results. Interestingly, the prognostic effect of CST1 is especially strong in stratified survival analysis of breast cancer, according to the factors attributed to worse outcome.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with this, the Kaplan–Meier survival analysis demonstrated that the OS and DFS of breast cancer patients with high CST1 expression were worse than those with low CST1 expression. High CST1 expression was also reported by previous studies to be linked to poor survival in colorectal cancer [40], pancreatic cancer [41], and non-small cell lung cancer patients [42], which was consistent with our results. Interestingly, the prognostic effect of CST1 is especially strong in stratified survival analysis of breast cancer, according to the factors attributed to worse outcome.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, we screened 98 DEGs which were observed in all the pancreatic cancer samples analyzed. Of these DEGs, some were previously recognized regulators associated with this malignancy, such as S100P [18], ITGA3 [19], ITGA2 [20], LAMC2 [21], SERPINB5 [22], SDC1 [23] and CST1 [24], some were identified involved in this disease for the first time (Table 1). Further validation of genes with altered expression was based on data from a different platform, which was of benefits in terms of evading platform-specific biases.…”
Section: Discussionmentioning
confidence: 99%
“…33, 34, 35 Paradoxically, CST1 has been proposed to be a novel marker in several tumors, including non-small cell lung cancer, pancreatic cancer, colorectal cancer and gastric cancer. 8, 9, 10, 11 The upregulated expression of CST1 is associated with proliferation, invasion and metastasis of cells, which are the main characteristics of tumor malignancy. 8, 10, 36 To date, the cooperative effect of CatB and CST1 during tumorigenesis remains poorly defined.…”
Section: Discussionmentioning
confidence: 99%
“…7 Cystatin SN (CST1), encoded by CST1, is a member of the type 2 cystatin family, and the induction of CST1 expression is associated with tumorigenesis, increased cancer cell proliferation and invasion, and tumor recurrence. 8, 9, 10, 11 As CatB is a functional protease and CST1 is its inhibitor, it is highly paradoxical that both of them contribute to tumorigenesis. To date, the underlying relationship between CST1 and CatB, and their roles in tumor development, remains poorly understood.…”
mentioning
confidence: 99%